2008
DOI: 10.1038/ni.1616
|View full text |Cite
|
Sign up to set email alerts
|

SLP-65 regulates immunoglobulin light chain gene recombination through the PI(3)K-PKB-Foxo pathway

Abstract: Although the essential role of the adaptor protein SLP-65 in pre-B cell differentiation is established, the molecular mechanism underlying its function is poorly understood. In this study, we uncover a link between SLP-65-dependent signaling and the phosphoinositide-3-OH kinase (PI(3)K)-protein kinase B (PKB)-Foxo pathway. We show that the forkhead box transcription factor Foxo3a promotes light chain rearrangement in pre-B cells. Our data suggest that PKB suppresses light chain recombination by phosphorylating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
161
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(172 citation statements)
references
References 49 publications
11
161
0
Order By: Relevance
“…This finding indicates that it is the absence of methylation programs. Recently, it was discovered that Foxo family transcription factors promote the differentiation of pre-B cells and that signals processed through Syk and the PI3K pathways counteract this activity by degrading Foxo proteins (Amin and Schlissel, 2008;Herzog et al, 2008). Our finding that the R→K198 mutation increases Syk and PI3K signaling of the BCR and reduces the differentiation signal of the pre-BCR is in line with these data.…”
Section: Ig Arginine Methylation Supports B Cell Differentiationsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding indicates that it is the absence of methylation programs. Recently, it was discovered that Foxo family transcription factors promote the differentiation of pre-B cells and that signals processed through Syk and the PI3K pathways counteract this activity by degrading Foxo proteins (Amin and Schlissel, 2008;Herzog et al, 2008). Our finding that the R→K198 mutation increases Syk and PI3K signaling of the BCR and reduces the differentiation signal of the pre-BCR is in line with these data.…”
Section: Ig Arginine Methylation Supports B Cell Differentiationsupporting
confidence: 89%
“…In addition, the BCR provides a survival signal that uses the PI-3 kinase (PI3K) pathway (Srinivasan et al, 2009). Recent findings suggest that Foxo family transcription factors also induce differentiation of pre-B cells, whereas signals from PI3K negatively control this process by causing the degradation of Foxo proteins (Amin and Schlissel, 2008;Herzog et al, 2008). Interestingly, protein arginine methyltransferase 1 (PRMT1) was found to methylate the Foxo1 protein, thereby inhibiting its phoshorylation and subsequent degradation (Yamagata et al, 2008).…”
Section: Br Ief Definitive Repor Tmentioning
confidence: 99%
“…This result is consistent with a previous report indicating that Akt regulates FoxO1 at the post-transcription level by phosphorylating FoxO1 and sequestering FoxO1 in the cytoplasm for degradation [32,33]. Rag-1, one of the downstream targets of FoxO1, mediates V-DJ recombination to generate BCR [15,34]. We observed that Rictor deletion induced an increase in Rag-1 at the mRNA and protein levels in B cells ( Figure 5).…”
Section: Rapamycin Treatment Aggravated the Defect In B Cells Inducedsupporting
confidence: 93%
“…14,15 It has subsequently been reported that the PI3K pathways suppressed RAG gene expression by means of PKB-mediated phosphorylation of FOXO transcription factors which promote RAG gene transcription. 16,17 CD19, together with CD21, CD81 and CD225 (Leu-13) is a vital component of the B lymphocyte antigen sensing pathway.…”
Section: Early B-cell Development Is Intact In P110δmentioning
confidence: 99%
“…[53][54][55] It was recently shown that Foxo1 directly regulates the transcription of the RAG-1-RAG-2 locus during B cell development. 16,17 Thus PI3K may also contribute to the suppression of RAG-gene transcription via activation of PKB, which has an inhibitory effect on FOXO transcriptional activity. The regulatory role of PI3K may be further increased by CD19 acting in concert with PI3K signaling or through other, PI3K-independent, pathways.…”
Section: Notementioning
confidence: 99%